Colisitn & Multidrug resistant Acinetobacter sepsis in a neonate - Raj, Gowri; Nair, P Madhava Chandran (Asian Journal of Clinical Pediatrics and Neonatology, 2015)
Acinetobacter infections are uncommon but, when they occur, usually involve organ systems that have a high fluid content. A. baumannii is intrinsically multidrug resistant. Relatively few antibiotics are active against this organism. We present here a case of multi drug resistant acinetobacter sepsis successfully treated with colistin, a previously abandoned polymyxin antibiotic.